A graphical user interface application for continuous-time identification of dynamical system - Rahmat, Mohd. Fua'ad; Omar, Rosli; Jamaluddin, Hishamuddin (Penerbit UTM Press, 2002)
This paper introduces a Graphical User Interface (GUI) application in system identification and parameter estimation of dynamic systems using Generalized Poisson Moment Functionals (GPMF) method based on Instrumental Variable (IV) algorithm. The GUI based on MATLAB consists of data preprocessing, parameter estimation, model validation and model simulation. A stepby-step instruction on how to use the GUI employed in the study is also presented. A validation process had been implemented using cross validation process. Simulation process based on the estimated mathematical model was performed to analyze the dynamic behaviors of the model. From the simulation results and analysis, it could be concluded that the model obtained using this GUI is reliable.